Linguistic features of persuasive communication - Komar, Smiljana (ELOPE (Ljubljana), 2015)
Direct response television commercials (DRTV) exhibit a very specific style of speech and delivery whose main function is to boost the product's value and sales. This paper presents the findings of the structural and the linguistic analyses of three English DRTV short form spots as seen on Highstreet TV. The emphasis is on the verbal strategies used by advertisers to get the consumers' attention, develop their interest and desire to own the product and to convince them to purchase it. These strategies include different lexical, syntactic and prosodic features. The structural analysis focuses mainly on non-verbal strategies of broadcasting advertisements whose purpose is to inspire interest and credibility in potential consumers.
Keywords: Coh-Metrix; kratki oglasi z neposrednim odzivom; leksikalna kompleksnost; model AIDA; prepričevalno sporazumevanje; prozodija; skladenjska kompleksnost; VocabProfile